Legal Protection for Workers with Disabilities in Indonesia: Implementation Analysis and Comparison with Japan from a Labor Justice Perspective - Alfarisi, Salman; Damayanti, Ratih (Semarang State University Undergraduate Law and Society Review, 2026)
Workers with disabilities in Indonesia continue to encounter deep and multifaceted barriers in entering and sustaining participation in the formal labor market because the implementation of national regulations that guarantee equal employment rights, workplace accessibility, and protection from discrimination remains inconsistent with the expectations set by existing legal frameworks, creating a significant gap between the normative commitments contained in disability and labor legislation and the realities experienced in workplaces that often underestimate the capabilities of disabled workers, maintain persistent social stigma, and fail to provide adequate facilities and organizational policies that support their effective participation. This study aims to explain the reasons why these barriers persist by examining how weak oversight, limited understanding among employers, inadequate workplace accessibility, minimal use of assistive technology, and the absence of strong incentive and sanction systems collectively undermine the objectives of disability inclusion policies. The findings reveal that companies often disregard hiring quotas, government institutions lack the capacity to enforce compliance, workplaces remain largely inaccessible, and small and medium-sized enterprises struggle to adopt inclusive practices due to resource limitations and insufficient technical guidance. In contrast, multinational companies that have implemented structured facilities, flexible work arrangements, and targeted training demonstrate that inclusion can operate effectively when supported by organizational commitment. Based on these findings, the study recommends strengthening institutional coordination, improving employer education on disability rights, expanding vocational and skills-based training tailored to various types of disabilities, enhancing accessibility facilities in workplaces, and providing clear and practical guidelines for companies of different sizes so they can adjust work environments, tasks, and policies in ways that allow workers with disabilities to participate more fully and sustainably in Indonesia’s labor market.